2021
DOI: 10.1088/1361-648x/ac40ad
|View full text |Cite
|
Sign up to set email alerts
|

Methanol carbonylation to acetaldehyde on Au particles supported by single-layer MoS2 grown on silica

Abstract: Homogenous single-layer MoS2 films coated with sub-single layer amounts of gold are found to isolate the reaction of methanol with carbon monoxide, the fundamental step toward higher alcohols, from an array of possible surface reactions. Active surfaces were prepared from homogenous single-layer MoS2 films coated with sub-single layer amounts of gold. These gold atoms formed clusters on the MoS2 surface. A gas mixture of carbon monoxide (CO) and methanol (CH3OH) was partially converted to acetaldehyde (CH3CHO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…19 Furthermore, carbonylation of methanol to acetaldehyde over Au clusters on single-layer MoS 2 films was also reported by Blair and co-workers (Scheme 3). 20 A partial of CO and methanol was transformed to acetaldehyde (14) under mild conditions (3.08 MPa and 120 °C). This carbonylation of methanol to a C2 species is a critical step toward the formation of higher alcohols from methanol.…”
Section: Synpacts Synlettmentioning
confidence: 99%
“…19 Furthermore, carbonylation of methanol to acetaldehyde over Au clusters on single-layer MoS 2 films was also reported by Blair and co-workers (Scheme 3). 20 A partial of CO and methanol was transformed to acetaldehyde (14) under mild conditions (3.08 MPa and 120 °C). This carbonylation of methanol to a C2 species is a critical step toward the formation of higher alcohols from methanol.…”
Section: Synpacts Synlettmentioning
confidence: 99%
“…This behavior is to be contrasted with the strong role played by vacancies in facilitating the chemical reactivity of 2D dichalcogenide MoS 2 [16] and points to the subtleties in the electronic and geometric structure of the trichalcogenides vs the dichalcogenides. Related work by Almeida et al [17] exposes the catalytic activity of a 2D composite catalysts consisting of Au nanoparticles supported on single layer MoS 2 grown on silica towards carbonylation of methanol to acetaldehyde. Accompanying density functional theory modeling provides a mechanistic understanding of this C2 bond formation that is a critical step toward the formation of higher alcohols.…”
Section: D Materialsmentioning
confidence: 99%
“…Related work by Almeida et al [17] exposes the catalytic activity of a 2D composite catalysts consisting of Au nanoparticles supported on single layer MoS 2 grown on silica toward carbonylation of methanol to acetaldehyde. Accompanying DFT modeling provides a mechanistic understanding of this C2 bond formation that is a critical step toward the formation of higher alcohols.…”
Section: D Materialsmentioning
confidence: 99%
“…Scanning electron microscopy showed that MoS 2 enhanced the formation of Au-rich aggregates on the surface of the catalysts during the synthesis, which played a vital role in the catalytic activity. 12 Peringer et al published in 1996 a more exotic synthesis route to AADMA and other dimethyl acetals starting from a palladium complex. They showed that by using tridentate ligand, as shown in Scheme 1, a general synthesis of dimethylacetals from alkynes can be conducted in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron microscopy showed that MoS 2 enhanced the formation of Au-rich aggregates on the surface of the catalysts during the synthesis, which played a vital role in the catalytic activity. 12 …”
Section: Introductionmentioning
confidence: 99%